Efeito de revestimento a base de xiloglucano enriquecido com extrato antioxidante do subproduto do caju sobre o amadurecimento de goiabas - Pontes, Claudilane Martins (2019)
The objective of this study was to evaluate the postharvest quality and antioxidant metabolism of guavas coated with xyloglucan (2% w/v), sesame oil (5% w/w) and antioxidant cashew extract (1% v/v). The guavas (Psidium guajava L.) of the 'Paluma' variety, after harvest, were divided into three groups consisting of Control (uncoated), RX (Xyloglucan and sesame oil coating) and RXE (Xyloglucan coating, oil sesame extract and Cashew antioxidant extract (EC)). After applying the treatments, the fruits were stored at 25 ºC for 14 days, and evaluated on days 0, 4, 7, 11 and 14 for the physical (loss of mass) and physicochemical (soluble solids, titratable acidity, pH and maturation index) variables; color and associated compounds (chlorophyll and carotenoids); firmness and physical integrity of the tissue (wall hydrolytic enzymes - PG and PME), lipid peroxidation and histology; and antioxidant metabolism (antioxidant and non - enzymatic compounds - ascorbic acid, total polyphenols), as well as the antioxidant metabolism (non - enzymatic antioxidant compounds - ascorbic acid, total polyphenols) and enzyme inhibitors (Superoxide Dismutase (SOD), Catalase (CAT) and Ascorbate Peroxidase (APX)), as well as Total Antioxidant Activity (AAT). The antioxidant coating delayed fruit ripening. Results showed that in relation to color and associated variables, RXE guavas presented chlorophyll degradation in longer time when compared to the control, showing as well the positive influence on synthesis of carotenoids. The coating protected against degradation of the cell wall of the fruit mesocarp, promoting lower levels of lipid peroxidation, consequently maintaining firmness. The antioxidant defense system was higher for RXE due to the higher content of ascorbic acid and polyphenols, as well as the activity of antioxidant enzymes. Results suggest that the antioxidant coating based on xyloglucan, sesame oil and EC consists of a post-harvest technology that could be applied to 'Paluma' guavas to improve fruit quality by promoting an increase in its defense antioxidant system, slowing the oxidative processes of ripening.